Public AI imaginaries: How the debate on artificial intelligence was covered in Danish newspapers and magazines 1956–2021 - Scott Hansen, Sne (Nordicom review, 2022)
This article investigates the media's construction of public perceptions of future human–machine relationships related to artificial intelligence (AI) development and reflects on how such perceptions play a role in shaping strategies for the use of AI in Denmark. Through a critical discourse analysis of 253 newspaper and magazine articles published from 1956 to 2021, it shows how conflicting discursive positions are constructed, representing what I refer to as public AI imaginaries. The analysis shows that newspapers and magazines tend not to distinguish between futuristic descriptions of the human–machine relationship of AI and the human-centred principles of intelligence amplification (IA). Furthermore, it demonstrates how principles of IA are reflected in the Danish strategies for AI in practice. While the discursive ambiguity has fuelled public debate, it leaves the term AI relatively vague, thereby creating uncertainty rather than possibilities for a form of human-centered AI in empirical reality.